Persepsi Mahasiswa Prodi Perpustakaan dan Sains Informasi Fakultas Teknologi Informasi terhadap Layanan Sirkulasi Perpustakaan O. Notohamidjojo UKSW - Titus Bara Kirana; Albertoes Pramoekti Narendra (Departement of Mathematics Education, 2023)
The university is a learning implementing agency for senior secondary education in the formal education pathway. This is in line with the definition of higher education as stipulated in Law Number 20, Article 19 (1) of 2003. Basically all libraries are collaborative processes, namely institutions that provide information services to users. However, each type of library has a determining interpretation in its development so that there is a difference from other libraries. The academic library is an example of the many classifications of libraries. The research method used in this research is a descriptive method with a quantitative approach. The purpose of this research was to find out students' perceptions of SWCU O. Notohamidjojo Library Circulation Services. The results of the research that have been explained from the discussion in the previous chapter, conclusions were obtained regarding students' perceptions of circulation services at the SWCU O. Notohamidjojo University Library.